Women's Psychological Responses in Various Conditions of Obstetric Problems; Phenomenological Analysis of Postpartum Mothers, Miscarriages, and At-Risk Pregnancy Conditions - Nanik Yuliwati; Alfa Hasanah; Een Ernalia; Lala Herawati; Yuni Hardani; Nurhayati; Awidevti Pakpahan; Putri Yunita Sari; Meika Anggraini Lestari; Siti Mutiah (Postgraduate, University of Mataram, 2025)
Pregnancy and childbirth are pivotal experiences in a woman’s life that involve not only physiological transformations but also intricate psychological adjustments. This study aims to explore and understand women’s psychological responses under various obstetric conditions, including postpartum, miscarriage, and high-risk pregnancies. A qualitative design with a phenomenological approach was employed to capture the essence of participants’ lived experiences. Data were collected through in-depth interviews and participant observation involving a total of 73 participants, consisting of 37 postpartum mothers as primary informants and 36 key informants (partners, healthcare professionals, and family members) from several regions in West Java and Banten. Data were analyzed using Colaizzi’s thematic analysis to identify patterns of emotional reactions and coping strategies among mothers facing different post-pregnancy conditions. The findings reveal distinct variations in psychological responses depending on the type of obstetric condition experienced. Mothers who underwent miscarriage or postpartum hemorrhage demonstrated higher levels of anxiety, sadness, and emotional distress compared to those with normal deliveries. Meanwhile, mothers with adequate social and familial support exhibited greater resilience and adaptability in managing emotional challenges. Problem-focused coping strategies were more prevalent among educated mothers with strong social networks, while emotion-focused coping was commonly found in those with limited support. In conclusion, this study emphasizes that social support and education play critical roles in shaping adaptive coping mechanisms and reducing psychological distress among women experiencing diverse obstetric conditions. Strengthening psychosocial interventions and community-based support systems is recommended to improve maternal mental health outcomes.